Pengaruh pemanfaatan teknologi informasi Blog edukatif tentang Hipertensi dan telepon terhadap tingkat pengetahuan penderita Hipertensi Di Wilayah kerja Puskesmas Wirobrajan. - Zulfa Mahdiatur Rasyida (PSIK 14 UMY 365, 2014)
*365 Background: Hypertension which is known as the "silent killer" that is one of the non-communicable diseases. It shows an increase in blood pressure over 140/90 mmHg. The prevalence of hypertension in the world in 2008 reached 40% and it was expected would be increase significantly by 2025. If hypertension is not treated, it could cause a variety of complications, namely enselopati (brain damage), kidney failure, myocardial infarction, heart failure, stroke, and death. The incidence of hypertension is influenced by several factors, one of them is knowladge. One of the efforts that can increase the knowladge is the providing health education by indirect method though u be used to encourage patients to do lifestyle modification is to increase knowledge throughutilization of information technology educational blog. Porpose: the aim of this study was to determine the effect of the utilization of information technology educational blog about hypertension and the telephone on the level of knowledge of hypertensive patients in WirobrajanPublic Health Care Center. Method: This research used Quasi Experiment with one group pre-post test design. The total samples were21 respondents that taken by purposive sampling method. Statistical tests that used was Wilcoxon Signed Ranks Test with significance level p> 0.05 level. Result:There is an increased level of knowledge of the respondents viewed based on the value of the pre-test (4.00) and post-test (11.22) with p value 0.00 . It shows that there is significant difference. Conclution:there is an influence of utilization of information technology educational blog about hypertension and phones to the level of knowledge of hypertensive patients was significantly. Keywords: information technology, educational blogs, hypertension, level of knowledge, knowledge, phone.